Examining the role of food bank knowledge, healthy food behaviors, and depression on family food insufficiencies - Landess, Mark W. (Kansas State University, 2013)
The Food Sufficiency Status Model is a conceptual model that was devised to help explain why some individuals are at an increased risk of becoming food insufficient. This model proposes that there are four factors that can influence an individual’s food status they are—demographics, family status/household size, food risk factors, and depression. This study uses data from the National Health and Nutrition Examination Survey (NHANES, 2007-2008)—Flexible Consumer Behavior Survey Module (n = 3,413), collected by the Centers for Disease Control and Prevention (CDC). The overall results generally supported the Food Sufficiency model and explained 22% (R[superscript]2adj = 0.215) of the variance in food sufficiency in the study’s population.
Keywords: Family Food Insufficiencies; Food Bank Knowledge; Food Insecurity; Depression; Healthy Food Behaviors; Food Insufficiencies; Food Science (0359); Individual & Family Studies (0628); Mental Health (0347)